Macroeconomic Impact of Product and Labor Market Reforms on Informality and Unemployment in India - Anand, Rahul (IMF Working Papers; Working Paper ;, 2016)
This paper investigates the implications of lowering formal regulations in labor and product markets on informality and macroeconomic outcomes in India. We estimate a DSGE model with an informal sector, and rigidities in the formal labor and product markets. Along with increasing GDP and employment, deregulation also leads to lower informality and greater product market competition. Slow reallocation of resources between the formal and informal sectors leads to some adverse impacts in the short run that can be minimized by implementing a combined package of reforms. These impacts are shown to be greater in an economy with a larger informal sector.